UJI EFEKTIVITAS DAN IDENTIFIKASI SENYAWA EKSTRAK BIJI SIRSAK (ANNONA MURICATA LINN.) YANG BERSIFAT BIOAKTIF INSEKTISIDA NABATI TERHADAP HAMA THRIPS - P., Mulyawati, A. (ALCHEMY, 2012)
Annona muricata grow widespread and they are known as herbal insecticides. The aim of this experiment is to: 1) evaluated of crude extracts against thrips pest and 2) known insecticides chemical compounds from crude extracts Annona muricata seeds. These extract with the concentration of 5 mg ekstrak/L air, 10 mg ekstrak/L air, 20 mg ekstrak/L air, 40 mg ekstrak/L air, and 80 mg ekstrak/L air were added to the thrips pest was had red bended at Jatropha curcas. Polysulfides and combine water dan detergen were used as positive control and negative control, respectively. Thrips pest were observed in 120 hours after spraying completed random program. Identification of insecticides bioactive compunds from crude extract Annona muricata seeds using thin layer chromatography (TLC), phytochemical analysis spectrofometer FTIR and Chromatography Gas-Spectra Mass (GC-MS). The result showed each concentration of crude extracts Annona muricata seeds have toxicity at thrips pest were showed in LC < 1000 mg extract/L air, exactly 16,9272 mg ekstrak/L water in 120 hours after spraying. Concentration 40 mg extract/L water in 72 hours  have kill 39,2%, is not significant difference with 80 mg extract/L water 44,4 % of mortality. Phytochemical analysis secondary metabolite and separatoring acetogenin compounds using analitic TLC done give negative result. The result identivication of FTIR and gas chromatograph-mass spectra (GC-MS) is unsaturated carboxilic acid; linoleic acid, octadecanoic acid, palmitic acid and 2furancarboxaldehide.